Effect of Microalloying on Microstructure and Mechanical Properties of Laser Weld of PHS Steel - Chunzhi Xia; Yinggang Liu; Xiaoguo Song; Famin Cong (Materials Research, 2023)
Abstract The laser welded joint of 2000MPa cold rolled annealed hot pressed steel (PHS) is easy to break during cold rolling. In this paper, the laser welding method is used to butt weld four kinds of PHS2000 with a thickness of 3.5mm. The four kinds of PHS2000 steel are added with elements of 0% Nb, 0.04% Nb, 0.06% Nb + Cr and 0.08% Nb + Cr. The microstructure of the four kinds of welded joints is compared and analyzed. The mechanical properties of the four kinds of joints are compared through hardness test and tensile test. The results show that after adding 0.04% Nb, residual austenite appears in the weld zone and fully quenched zone, the width of columnar crystal decreases, the average hardness of the weld zone decreases from 595HV to 408HV, and the tensile strength increases from 608MPa to more than 800MPa. For chromium containing steel, the increase of niobium content can reduce the size of columnar crystal in weld zone.